Potential Test of Sulphate Reducing Bacteria (SRB) To Changes the Acidity of Sulphate Acid Soil and Corn Growth with Different Water Content in Green House - yudi sudarno sihombing; Asmarlaili Sahar Hanafiah; Mariani Sembiring (Jurnal Agroekoteknologi, 2018)
This study aimed to determine the potential for a superior sulphate reducing bacteria (SRB) from  tested on acid sulfate soil with different water content. The research activities carried out in the Laboratory of Soil Biology and Green House of Faculty Agriculture, University of North Sumatra. The research used Randomized Block Design with 2 treatments : SRB isolate (control, LK4, LK6, TSM4, TSM 3, AP4,  AP3, LK4+TSM3, LK4+AP4, LK4+AP3, LK6+TSM3, LK6+AP4, LK6+AP3, TSM4+TSM3, TSM4+AP4, TSM4+AP3) and water condition (100% field capacity and 110% field capacity). The results shown application of  isolate LK4+AP4 with water condition 110% field capacity decreased the soil sulphate content (27,38 ppm) significantly after week 6.  Application of  isolate LK4+AP3 with water condition 110% field capacity increase soil pH (5,58) significantly after week 6. Application of  isolate LK4 with water condition 110% field capacity increase the plant growth (140 cm; 25,74 g) significantly after week 6. The best treatment was application isolate LK4 with water condition 110% field capacity (RBS population 2,5x108; soil sulphate content  29,10ppm; soil acidity 4,78; plant height 140cm; plant weight 25,74gr).   Keywords       : pH, Soil Sulphate Content, Sulphate Reducing Bacteria, Water Condittion.